Successful Management of Fulminant Guillain-Barré Syndrome and Its Complications. Issue 5 (May 2018) - Kamei, Atsushi; Akasaka, Manami; Araya, Nami; Ishikawa, Ken; Takada, Akira; Furukawa, Hiromi; Tanifuji, Sachiko; Asami, Maya; Nasu, Yurie; Oyama, Kotaro; Chida, Shoichi
Abstract : Abstract: A 3-year-old girl presented with muscle weakness of her limbs and trunk 6 days after developing symptoms of common cold. Two days later, she experienced respiratory arrest with a Glasgow Coma Scale score of 3, necessitating endotracheal intubation. Therefore, she was transferred to our hospital with suspected acute encephalopathy. Although no abnormalities were observed on brain and spinal magnetic resonance imaging and electroencephalography, peripheral nerve conduction velocity tests failed to evoke motor and sensory nerve action potentials. Thus, we gave a diagnosis of fulminant Guillain-Barré syndrome and initiated immunoglobulin therapy. On day 3 of admission, she developed sinus tachycardia that induced circulatory failure and oliguria, which was successfully treated with landiolol. Subsequently, we performed plasmapheresis followed by immunoglobulin and steroid pulse therapies. She was weaned off the mechanical ventilator by day 20 of admission, was ambulatory by day 44, and had completely recovered without any adverse sequelae by day 55. In conclusion, landiolol was effective for treating acute sinus tachycardia–induced circulatory failure and played a key role in saving the life of this patient.